Exercise 4.7 (b) : Show that under Assumptions 4.10 and 4.11, $T:H(X) \to H(X)$.

$H(X)$ is the set of continuous and homogeneous of degree one functions and $Tf(x) = \sup_{y \in \Gamma(x)} \{F(x,y) + \beta f(y)\}$. The continuity follows from the theorem of maximum. I am a little confused with showing $Tf$ is homogeneous of degree one. According to the solution, \begin{equation} \begin{split} Tf(\lambda x)& = \sup_{\lambda y \in \Gamma(\lambda x)} \{F(\lambda x,\lambda y) + \beta f(\lambda y)\}\\ & = \lambda \sup_{y \in \Gamma(x)} \{F(x,y) + \beta f(y)\} \\ & = \lambda Tf(x). \end{split} \end{equation} $\lambda$ can be taken out of functions because they are homogeneous of degree one. But, how can we justify the change from $\Gamma(\lambda x)$ to $\Gamma(x)$? More precisely, \begin{equation} \begin{split} Tf(\lambda x)& = \sup_{\lambda y \in \Gamma(\lambda x)} \{F(\lambda x,\lambda y) + \beta f(\lambda y)\}\\ & = \lambda \sup_{\lambda y \in \Gamma(\lambda x)} \{F(x,y) + \beta f(y)\} \\ & = \lambda \sup_{y \in \Gamma( x)} \{F(x,y) + \beta f(y)\} . \end{split} \end{equation} I do understand the second equality, but I do not understand the third equality.

Assumption 4.10 and 4.11 are as follows: enter image description here


It follows from Assumption 4.10.

Let $\lambda y \in \Gamma(\lambda x)$ be the solution.

Let $\delta = \frac{1}{\lambda}$.

By Assumption 4.10,

$$ \lambda y \in\Gamma(\lambda x) $$ implies $$ \delta \lambda y \in \Gamma(\delta\lambda x) $$ in other words $$ y \in \Gamma(x) $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.